Anna Maria van Schurman: Letters and Poems to and from Her Mentor and Other Members of Her Circle: edited and translated by Anne R. Larsen and Steve Maiullo, The Other Voice in Early Modern Europe, the Toronto Series, 81, New York and Toronto, Iter, 2021, 402 pp., $65.95, ISBN 978-1-64959-012-1 - Maxwell, Felicity Lyn (Women's Writing, 2023)
There are nineteen letters and twenty-one poems from Huygens, with eight letters and thirteen poems by Van Schurman; the Latin and Dutch originals of their poems are also included. 2021, 402 pp., $65.95, ISBN 978-1-64959-012-1 Appendix D is a translation of a little-known biography of Van Schurman, embedded in a biography of Jean de Labadie.